2023
DOI: 10.3390/jcm12041293
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of Allogeneic Red Blood Cell Transfusions in Non-Bleeding Patients in a Large Teaching Hospital: A Retrospective Study

Abstract: In hemodynamically stable patients, both anemia and red blood cell (RBC) transfusion may be detrimental to patients; hence, a decision regarding RBC transfusion should be based on thorough risk–benefit assessment. According to hematology and transfusion medicine organizations, RBC transfusion is indicated when recommended hemoglobin (Hb) triggers are met, and symptoms of anemia are present. The aim of our study was to examine the appropriateness of RBC transfusions in non-bleeding patients at our institution. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Numerous studies point out that PC or RBC transfusions are performed outside of the recommendations provided in guidelines [ 15 , 20 ]. In our study, we showed that approximately 56% of all PC transfusions were not compliant with the most recent PC transfusion guidelines [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies point out that PC or RBC transfusions are performed outside of the recommendations provided in guidelines [ 15 , 20 ]. In our study, we showed that approximately 56% of all PC transfusions were not compliant with the most recent PC transfusion guidelines [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to numerous possible complications, if PC is used outside the recommended indications, patients are put at risk. Poor implementation of blood component transfusion guidelines leads to over-transfusion, as the authors showed in the previous publication regarding red blood cells (RBC) [ 15 ]. Over-transfusion of PC also decreases the availability of this scarce resource, which is particularly important during pandemics when recruitment of donors is compromised, an example being the novel coronavirus disease (COVID-19) pandemic [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transfusion of blood products can lead to numerous complications, the frequency of which depends on the blood product being transfused. These complications comprise febrile non-hemolytic transfusion reactions, acute hemolytic transfusion reactions, nosocomial infections, immunomodulation, transfusion-associated acute lung injury (TRALI), thromboembolic complications, allergic reactions, immunization, and blood-born pathogen transmission [6]. The leading cause of death following transfusion is transfusion-associated circulatory overload [7], particularly following high-volume (standard dose 20 mL/kg) FFP transfusions [8].…”
Section: Article Information and Declarationsmentioning
confidence: 99%
“…The appropriateness of RBC transfusions was decided based on Hb concentration and signs and/or symptoms of anemia before transfusion. Anemia symptoms had to be present before transfusion despite attempts to improve the patient’s tolerance to anemia through increased oxygenation and hemodynamic optimization [ 6 , 7 ]. Increased oxygenation involved oxygen therapy aimed at peripheral oxygen saturation (SpO 2 ) of 100% and/or arterial oxygen saturation (paO 2 ) of 200 mm Hg.…”
mentioning
confidence: 99%